9ª CONGRESSO GOIANO DE FISIOTERAPIA RESPIRATÓRIA, CARDIOVASCULAR E TERAPIA INTENSIVA DA ASSOBRAFIR (Movimenta (ISSN 1984-4298), 2022)
9ª CONGRESSO GOIANO DE FISIOTERAPIA RESPIRATÓRIA, CARDIOVASCULAR E TERAPIA INTENSIVA DA ASSOBRAFIR